Comparison of color difference and reliability of two intraoral spectrophotometers - Sanaa N. Al-Haj Ali; Ra'fat I, Farah; Abdullah Aldhefeeri; Ibrahim Alduraibi (Universidade Estadual de Campinas, 2021)
Aim: to evaluate the intra and inter-device reliability of two intraoral spectrophotometers in measuring the Commission Internationale de l'Éclairage (CIE) L*a*b* color coordinates and to compare the color difference (ΔE) between both devices. Methods: the central region of the labial surface of the maxillary central incisor of 31 participants was measured twice by each of the devices (VITA EasyShade and Degudent Shadepilot) by one examiner. CIE L*a*b* color coordinates were obtained for all teeth and ΔE was measured and compared. Intraclass correlation coefficient (ICC) and Mann-whitney U test were used to analyze the data (p<0.05). Results: inter-device reliability ICCs in measuring CIE L*a*b* color coordinates ranged between 0.08-0.49 with significant difference between devices only concerning the b coordinate (p<0.05). While intra device reliability ICCs ranged between 0.86-0.89 for VITA EasyShade and 0.81-0.86 for Degudent Shadepilot. The mean ΔE for CIE L*a*b* color coordinates of VITA EasyShade was 3.61 (±1.93) compared to 3.60 (± 1.45) for Degudent Shadepilot with insignificant difference between both devices (p>0.05). Conclusions: high intra device reliability in measuring CIE L*a*b* color coordinates was achieved particularly of Vita EasyShade, and both devices had clinically acceptable color difference (ΔE <3.7) however, inter device reliability was low to moderate. Consequently, the same spectrophotometer should be used throughout the steps of performing any tooth- colored restoration.